The three levels of interest sought by Islamic legislation - Aklo, Ghassan (Al-Adab Journal, 2025)
The interest sought from legislating the provisions of Sharia law is divided into several categories, the clearest and most famous of which is its division based on importance and what the legislation relates to. It has come into ranks in existence in proportion to the strength of each of them in itself and the consequences of each of them. These ranks are termed the three levels, and discussion of them will be comprehensive. On a statement, examples and applications of many of them, and those three levels are the types of interests considering their strength in themselves, which are: (necessary interests), (necessary interests), (improving interests).